Microwave characterization of pandanus atrocarpus as potential organic-based dielectric substrate - Mohd Aziz Aris; Nurfarahin Miswadi; Suhaila Subahir; Hajar Jaafar; Fatimah Nur Mohd Redzwan (Institute of Advanced Engineering and Science, 2022)
This study investigated the microwave characterization of a potential organic-based substrate pandanus atrocarpus. Pandanus atrocarpus, also known as